Surgical Masks or N95 respirators for OMF Surgery during COVID-19 pandemic (2020)
Purpose: Coronavirus Disease 2019 (COVID-19) has caused suffering and death around the world. Careful selection of facial protection is paramount for preventing virus spread among healthcare workers and preserving mask and N95 respirator supplies. Methods: This paper is a comprehensive review of literature written in English and available on Pubmed comparing the risk of viral respiratory infections when wearing masks and N95 respirators. Current international oral and maxillofacial surgery guidelines for mask and N95 respirator use, patient COVID-19 disease status, aerosol producing procedures were also collected and incorporated into a workflow for selecting appropriate facial protection for oral and maxillofacial surgery procedures during the current pandemic. Results: Most studies suggest N95 respirators and masks are equally protective against respiratory viruses. Some evidence favors N95 respirators, which are preferred for higher risk procedures when aerosol production is likely or when the COVID-19 status of a patient is positive or unknown. N95 respirators may also be used for multiple patients or reused depending on the type of procedure and condition of the respirator after each patient encounter. Conclusion: N95 respirators are preferred over masks against viral respiratory pathogens, especially during aerosol generating procedures or when a patient’s COVID-19 status is positive or unknown.